Scale development of a winescape - Thomas, Ben; Quintal, Vanessa (School of Marketing, Curtin Business School, 2010)
This exploratory study aims to conceptualise the commonly referred to "winescape" construct and develop a winescape scale that can be used to predict wine tourist behaviour. The scale development adopted procedures suggested by Churchill (1979) and DeVellis (2003). A total of 262 tertiary students were sampled from a university in Western Australia that was within a three-hour radius of two well recognised wine regions - Swan Valley and Margaret River. The scale items exhibited reliability, convergent and discriminant validity. Additionally, six winescape factors including service staff, layout, setting, food and wine, non-wine related activities and cottage industries produced significant relationships with satisfaction with a wine region, demonstrating predictive validity.